Danish farmer cooperatives: Development, importance and lessons - Hansen, Henning Otte (Cooperativismo & Desarrollo, 2021)
The Danish farmer-owned cooperatives started back in the 1880s. The overall aim was to ensure farmers’ market power and market access in the marketing chain. Since then, cooperatives have emerged in most major agricultural and food industries. In certain industries, the market shares of cooperatives are large and dominant (pig meat, dairy, fur, feedstuff, etc.). In other sectors, market shares are smaller, and in some sectors, cooperative ownership has completely ceased (sugar, poultry, etc.). There are several significant drivers behind and explanations why developments have been so different. Cooperative ownership is found only in the agricultural supply and processing sectors, while farms are mostly owned and managed by the individual farmers. A number of prerequisites have been crucial for the significant development of the Danish farmer cooperative industry: A top-down approach has been important, so that farmers themselves have driven the development and have had strong incentives to strengthen the cooperative model. A certain level of social capital, a human cohesion, a certain level of education as well as a certain degree of trust and access to infrastructure have also been important factors. Today, the development and importance of cooperatives is recognized as a key driver behind the strong international competitiveness of the agricultural and food sectors in Denmark. Based on the experience and drivers behind the Danish cooperative model and on experience and reflections from less developed countries, opportunities and barriers to transferring Danish cooperative experiences to other countries are analyzed and evaluated. The results in terms of market access, etc. meet the needs of farmers in many less developed countries. However, a number of barriers are identified, and the cooperative model must be adapted to the specific circumstances in individual countries